A very large antenna for the 1.8 MHz band. - Christman, Al (IEEE Antennas & propagation magazine.)
This article describes a large 1.8 MHz antenna system that generates significantly more forward gain than that produced by commonly-used phased-vertical arrays. It provides coverage of all four azimuthal quadrants, along with a choice of four elevation angles, which may be selected at the turn of a switch.